Elaboration of goji berry jam, produced by hand, with the addition of pectin from the passion fruit peel (Research, Society and Development, 2020)
Goji Berry has many beneficial properties, as it is a fruit rich in zinc, vitamins A, C and E, riboflavin (vitamin B2), beta-carotene, lycopene and taurine. The objective of this work was to make a Goji Berry jam using the pectin obtained from the passion fruit peel. The raw material for the preparation of the jelly was purchased at Ceasa do Distrito Federal, the preparation was carried out in the technical and dietary laboratory of the Centro Universitário Planalto do Distrito Federal - UNIPLAN. Sensory analysis was carried out with 60 individuals, being only employees and students of UNIPLAN. The method applied was the hedonic scale, which is an affective method, and was a structured verbal scale. The values assigned to each item were analyzed and the results were positive in relation to the acceptance rate, all above 80%.